'Brothers in arms': Jewish self-defense during the Civil War in Ukraine, 1917–1921. Issue 4 (2nd October 2022) - Alroey, Gur
ABSTRACT: The novelty of this article is in the attempt to examine the pogroms from the point of view of the Jewish defenders and not of the victims or of the Ukrainian and Bolshevik establishment. Self-defense during the civil war in Ukraine played a historic role in the life of the Jewish towns. It stood guard and prevented killing and robbery. Helped in the restoration of economic and cultural life after the destruction of the community and its institutions. The focus on self-defense allows us to examine lesser-known and perhaps dark aspects of the Jewish self-defense in Ukraine.